Chlamydia and Its Many Ways of Escaping the Host Immune System. (6th August 2019) - Wong, Won Fen; Chambers, James P.; Gupta, Rishein; Arulanandam, Bernard P.
Abstract : The increasing number of new cases of Chlamydia infection worldwide may be attributed to the pathogen's ability to evade various host immune responses. Summarized here are means of evasion utilized by Chlamydia enabling survival in a hostile host environment. The pathogen's persistence involves a myriad of molecular interactions manifested in a variety of ways, e.g ., formation of membranous intracytoplasmic inclusions and cytokine-induced amino acid synthesis, paralysis of phagocytic neutrophils, evasion of phagocytosis, inhibition of host cell apoptosis, suppression of antigen presentation, and induced expression of a check point inhibitor of programmed host cell death. Future studies could focus on the targeting of these molecules associated with immune evasion, thus limiting the spread and tissue damage caused by this pathogen.